The official DataCAD user's guide - Smith, Michael R. 1965- (McGraw-Hill, 2000)
Written for the new 9.0 release by DataCAD staff, the hands-on Official Datacad User's Guide puts at your fingertips a complete A to Z guide to the use of this single most popular architecture-specific CAD program. Authors Michael Smith, Richard Morse, and Shelly Flanigan provide you with a tool that clarifies new features of the software, include the ability to externally reference other drawing files(XREF) and open multiple documents at the same time for cutting and pasting.